Kontribusi Keseimbangan dan Koordinasi Mata Kaki Terhadap Sepak Sila dalam Permainan Sepak Takraw pada Atlet Kota Sungai Penuh - Idial Gustira; Cundra Bahar; Roki Putra (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2024)
The problem addressed in this research is the low proficiency in the sepak sila skills among athletes in the city of Sungai Penuh. The objective of this study is to determine the contribution of balance and eye-foot coordination to sepak sila takraw performance among athletes in the city of Sungai Penuh in the year 2023. The research design employed in this study is correlational genfa. The sample size for this research consisted of 16 individuals. The research instruments used included balance tests, eye-foot coordination tests, and sepak sila tests. The data analysis technique utilized correlation tests and calculation of contribution values. The findings of the research lead to the following conclusions: (1) There is a 90% contribution of balance to sepak sila performance among sepak takraw athletes in the city of Sungai Penuh in the year 2023. (2) There is a 91% contribution of eye-foot coordination to sepak sila performance among sepak takraw athletes in the city of Sungai Penuh in the year 2023. (3) There is a 96% contribution of both balance and eye-foot coordination to sepak sila performance among sepak takraw athletes in the city of Sungai Penuh in the year 2023.